2014
DOI: 10.1007/s11064-014-1343-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Treatment with Quercetin on Cognition and Mitochondrial Function in a Mouse Model of Alzheimer’s Disease

Abstract: Amyloid-β (Aβ)-induced mitochondrial dysfunction has been recognized as a prominent, early event in Alzheimer's disease (AD). Therefore, therapeutics targeted to improve mitochondrial function could be beneficial. Quercetin, a bioflavanoid, has been reported to have potent neuro-protective effects, but its preventive effects on Aβ-induced mitochondrial dysfunction and cognitive impairment have not been well characterised. Three-month-old APPswe/PS1dE9 transgenic mice were randomly assigned to a vehicle group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(113 citation statements)
references
References 67 publications
2
108
1
2
Order By: Relevance
“…These findings are compatible with one previous study showing partial retention of ventilatory acclimatization using noninvasive indices of oxygenation and end tidal CO 2 levels after eight days at low altitude [2,54]. The drop in [Hb] from ALT16 to POST7/21 may be due to selective destruction of the youngest circulating red cells (neocytolysis) upon return to low altitude [55][56][57][58], or potentially an increase in plasma volume [59]. Physiological Retention of Acclimatization: Acute Mountain Sickness…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These findings are compatible with one previous study showing partial retention of ventilatory acclimatization using noninvasive indices of oxygenation and end tidal CO 2 levels after eight days at low altitude [2,54]. The drop in [Hb] from ALT16 to POST7/21 may be due to selective destruction of the youngest circulating red cells (neocytolysis) upon return to low altitude [55][56][57][58], or potentially an increase in plasma volume [59]. Physiological Retention of Acclimatization: Acute Mountain Sickness…”
supporting
confidence: 91%
“…These changes in acid-base buffering capacity, in both the arterial and CSF compartments, would lead to a greater rise in arterial and CSF [H ϩ ] for a given rise in Pa CO 2 . In support of this notion, lowering CSF bicarbonate concentration elevates the cerebrovascular CO 2 reactivity in an anesthetized dog model (27), whereas bicarbonate infusion increases cerebral perfusion pressure in patients with posttraumatic head injury (9), elevates cerebral blood volume in preterm infants (57), and lowers ventilation in healthy exercising humans at SL (44). As such, it has been suggested that the MCAv responses to CO 2 at high altitude are linked to changes in arterial acid-base balance (16,25).…”
Section: Effects Of Acclimatization On Cerebrovascular Co 2 Reactivitymentioning
confidence: 97%
See 1 more Smart Citation
“…Mitochondrial samples were assayed for ATP content using the ATP dependence of the light emitting luciferase-catalyzed oxidation of luciferin. ATP concentration was calculated according to a standard curve and related to protein content [45].…”
Section: Measurements Of Membrane Potential Ros and Atp Levelmentioning
confidence: 99%
“…Quercetin also displays antiamyloidogenic properties, illustrated by its ability to reduce BACE1 and Aβ levels in mice (217), prevent Aβ aggregation (221,222), promote autophagy (221,223) and bind to BACE1 catalytic core as an inhibitor (224). On the other hand, quercetin enhances the effect of neurotrophic factors such as NGF (225) and BDNF (226) to foster neuronal survival and neurite outgrowth, with tangible amelioration of memory function in animal models of AD (227)(228)(229)(230)(231) and in In parallel, XBP1 can be locally synthetized within dendrites through SPRCs and transported into the nucleus to activate transcription of BDNF, Kalirin-7 and a myriad of other genes that are crucial for the survival and plasticity of neurons. mBDNF is released at synapses and activates TrkB receptors to recruit XBP1 and Kalirin-7, which controls spinogenesis through Rho-GTPases RAC1 and PAK1, resulting in a positive activation loop.…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%